Genomic Testing for Human Health and Disease Across the Life Cycle: Applications and Ethical, Legal, and Social Challenges - Gemma A. Bilkey; Gemma A. Bilkey; Belinda L. Burns; Emily P. Coles; Faye L. Bowman; John P. Beilby; John P. Beilby; Nicholas S. Pachter; Nicholas S. Pachter; Gareth Baynam; Gareth Baynam; Gareth Baynam; et al. (Frontiers Media S.A., 2019)
The expanding use of genomic technologies encompasses all phases of life, from the embryo to the elderly, and even the posthumous phase. In this paper, we present the spectrum of genomic healthcare applications, and describe their scope and challenges at different stages of the life cycle. The integration of genomic technology into healthcare presents unique ethical issues that challenge traditional aspects of healthcare delivery. These challenges include the different definitions of utility as applied to genomic information; the particular characteristics of genetic data that influence how it might be protected, used and shared; and the difficulties applying existing models of informed consent, and how new consent models might be needed.